ADSORPTIVE REMOVAL OF HAZARDOUS INORGANIC ELEMENTS FROM WATER BY USING ORANGE WASTE - Katsutoshi Inoue (Universitas Gadjah Mada, 2008)
Pectic acid contained in some fruits like orange and apple is natural chelating polymeric material, exhibiting excellent adsorption behavior for some cationic metal ions including toxic heavy metals such as lead and copper. In addition, it also exhibits excellent adsorption behavior for some hazardous inorganic anionic species like phosphorus, arsenic and fluoride by loading some high valence cationic metal ions like zirconium(IV) in advance.For the practical application to the removal of these hazardous inorganic elements from various waste water at cheap cost, orange juice residue was employed instead of pure pectic acid. Orange juice residue just after juicing was activated by saponification with small amount of calcium hydroxide to prepare the sorbent.Some hazardous cationic species like lead(II), copper(II) and cadmium(II) were effectively adsorbed on this sorbent, while toxic anionic species like phosphate, arsenate, arsenite and fluoride were also effectively adsorbed on zirconium(IV)-loaded sorbent.